Uniconazole increases starch content in duckweed (Lemna aequinoctialis Welw.) - Ahmad Faizal; Rahman Tri Putra (3BIO: Journal of Biological Science, Technology and Management, 2019)
Uniconazole has been used to improve starch production in plants through the regulation of endogenous hormone levels. Here, we reported the effect of this compound on the starch accumulation in a duckweed plant (Lemna aequinoctialis). L. aequinoctialis was grown in Hoagland medium supplemented with different uniconazole concentrations: 400, 800, and 1600 mg/L. The results showed that treatment with 800 mg/L uniconazole significantly increased plant growth rate, doubling time and its chlorophyll content. Consequently, the starch content also increased by 1.5 fold upon treatment with 800 mg/L uniconazole. We, therefore, concluded that uniconazole treatment offers an effective means to enhance the production of starch in L. aequinoctialis.